Possible mechanisms of daylight duration and frequency of endometrium hyperplasia development - Chumak, Z. V.; Zelinsky, A. A.; Shapoval, N. V. (Journal of Education, Health and Sport, 2017)
Chumak Z. V., Zelinsky A. A., Shapoval N. V. Possible mechanisms of daylight duration and frequency of endometrium hyperplasia development. Journal of Education, Health and Sport. 2017;7(1):449-459. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.293055 http://ojs.ukw.edu.pl/index.php/johs/article/view/4274 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2017; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2017. Revised 16.01.2017. Accepted: 24.01.2017. POSSIBLE MECHANISMS OF DAYLIGHT DURATION AND FREQUENCY OF ENDOMETRIUM HYPERPLASIA DEVELOPMENT Z. V. Chumak2, A. A. Zelinsky1, N. V. Shapoval1 1Odessa National Medical University 2Odessa Municipal Centre for Menopause Problems nymba@mail.ru Summary The objective: to learn correlation of daylight duration and frequency of endometrium proliferous processes development. Retrospective analysis of case histories, patients’ histological journals with pathologically verified diagnosis of endometrium proliferous processes have been analyzed. All the patients referred to the clinics of the 5th maternity house at 2011-2014. The following groups were formed: hyperplasia of endometrium - simple complex hyperplasia without atypia; atypical hyperplasia of endometrium- simple complex hyperplasia with atypia; polyps of endometrium; adenocarcinoma. At the comparison of the daylight mean duration and frequency of proliferation atypical forms the instability between the parameters under study has been revealed. Comparison of the real levels of melatonin secretion at day and night time, mean duration of the daylight and frequency of endometrium’s proliferation show the presence of a hidden correlation at the condition of different statistical models of mathematical processing of the data use. Key words: pineal gland, melatonin, hyperplasia of endometrium, biological rhythm, proliferation.